Beyond individual justice facets: How (Mis)alignment between justice climates affects customer satisfaction through frontline customer extra-role service behavior. Issue 6 (2nd November 2018) - Tremblay, Michel; Chênevert, Denis; Vandenberghe, Christian; Parent-Rocheleau, Xavier
ABSTRACT: This study examines the combined effect of organizational justice facets on store-level customer extra-role service behavior, and subsequently on customer satisfaction. Hypotheses were tested on a sample of 1, 951 employees in 121 business units from four countries, and on 55, 731 customers of an international retailer. The results of polynomial regression and response surface analysis revealed that unit customer service performance and customer satisfaction are higher when justice facets are aligned at high levels, compared to when they are aligned at low levels. Moreover, we found evidence that the consequences of misalignment between justice facets are asymmetrical. Unit outcomes were higher when distributive justice (DJ) and procedural justice (PJ) climates were both higher than the interpersonal justice climate, compared to when the inverse was true. Conversely, unit outcomes increased when informational justice (INF-J) climate was higher than DJ and PJ climates, compared to when DJ and PJ climates were higher than INF-J climates. The observed effects of misalignment between justice facets were non-linear, as complex curvilinear relationships were moderator-dependent. Customer satisfaction was higher in stores with higher team customer service behavior, and team service behavior was found to be a significant conduit by which justice facets (mis)alignment influence customer satisfaction.